2021
DOI: 10.3390/ani11071988
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Monensin for Ketosis Prevention in Dairy Cows during the Transition Period: A Systematic Review

Abstract: Since the approval by the European Medicines Agency in 2013 of a monensin controlled-release capsule (CRC) for the prevention of ketosis in dairy cows, there has been widespread use across Europe. In recent decades, several papers have investigated the effects of monensin used as a CRC or as a feed additive to improve cattle energy metabolism and improve feed efficiency. Since the CRC is the only form of monensin permitted in Europe in dairy cows, the objective of this review was to report and summarize observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 53 publications
0
22
0
1
Order By: Relevance
“…Finally, treatments that are classically adopted in transition cows to modulate rumen fermentation, recently revealed to have a potential role in mitigating the immune dysfunction occurring immediately before and after parturition. Monensin is known for its effect on rumen bacteria populations, resulting in increased propionic acid and reduced lactic acid and methane production [67,120,121]. Thus, modulation of rumen fermentation through monensin is an effective strategy to address the risk of both ketosis and acidosis in dairy cows at the onset of lactation [122].…”
Section: Nutritional Strategies and Modulatory Treatments To Improve ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, treatments that are classically adopted in transition cows to modulate rumen fermentation, recently revealed to have a potential role in mitigating the immune dysfunction occurring immediately before and after parturition. Monensin is known for its effect on rumen bacteria populations, resulting in increased propionic acid and reduced lactic acid and methane production [67,120,121]. Thus, modulation of rumen fermentation through monensin is an effective strategy to address the risk of both ketosis and acidosis in dairy cows at the onset of lactation [122].…”
Section: Nutritional Strategies and Modulatory Treatments To Improve ...mentioning
confidence: 99%
“…Thus, modulation of rumen fermentation through monensin is an effective strategy to address the risk of both ketosis and acidosis in dairy cows at the onset of lactation [122]. These positive effect of monensin on rumen fermentation is reflected by trends of several plasma analytes (i.e reduced BHB and NEFA concentrations and higher plasma glucose) in cows treated with monensin [120,121,123]. A recent study [124,125] found reduced infiltration of T and B leukocytes in the rumen fluid from transition dairy cows that received a controlled-release capsule of monensin 21 days before the expected calving date (expected release rate, 335 mg/d for 95 days).…”
Section: Nutritional Strategies and Modulatory Treatments To Improve ...mentioning
confidence: 99%
“…Earlier reports suggested that nutrient partitioning and other metabolic activities are the essential physiological processes that subsequently help in subclinical ketosis (SCK) prevention (3) and improving cow's health during the transition and early lactation periods of dairy cattle. In general, the fatty acids, blood metabolites and GH directly or indirectly influence animals in terms of growth, reproduction, welfare condition, during the transition and early lactation periods (4)(5)(6)(7). During the early lactation period, dairy cows experience tremendous physiological and metabolic changes (8)(9)(10), accompanied by fetal development, milk production, high energy intake and a negative energy balance (NEB).…”
Section: Introductionmentioning
confidence: 99%
“…Dietary fat and trace mineral supplementations are also helpful in this regard [199,200]. Monensin supplementation significantly reduces the incidence of subclinical ketosis [201]. Injections of growth hormones such as recombinant bovine somatotropins (rbSTs) are also helpful in improving the metabolic profile and immunity of postpartum dairy cows [202,203].…”
Section: Effect Of High-protein Diet On Reproductive Performancementioning
confidence: 99%